Dentition Patterns in Different Unilateral Cleft Lip Subphenotypes. (December 2017) - Asllanaj, B.; Kragt, L.; Voshol, I.; Koudstaal, M.; Kuijpers, M.A.; Xi, T.; Bergé, S.J.; Vermeij-Keers, C.; Ongkosuwito, E.M.
Oral clefts play an essential role in disturbed odontogenesis of the deciduous and permanent dentition, yet little is known about this relationship. We investigated, within the categories cleft lip with or without alveolus (CL ± A) and cleft lip, alveolus and palate (CLAP), whether different CL subphenotypes based on morphological severity of the cleft show different dentition patterns and whether a more detailed subdivision of the incomplete CL has clinical relevance. In this retrospective study, 345 children with nonsyndromic unilateral CL ± A and CLAP from the Dutch Association for Cleft Palate and Craniofacial Anomalies (NVSCA) registry were included to assess the association between the CL subphenotypes and lateral incisor patterns. Five different deciduous and permanent patterns of the lateral incisor were distinguished: located in normal position (pattern z/Z), in the anterior segment (pattern x/X) or in the posterior segment of the cleft (pattern y/Y), one in each segment of the cleft (pattern xy/XY), and agenesis of the lateral incisor (pattern ab/AB). Analyses were performed by using multinomial logistic regression models. Children born with a vermillion notch or a one-third to two-thirds CL were most likely to have a deciduous pattern x and a permanent pattern X, while children born with a two-thirds to subtotal CL were most likely to have deciduous pattern xy and a permanent pattern X compared to children with a complete CL that predominantly had deciduous pattern y and a permanent pattern AB. Based on the relationship of the CL morphology with the deciduous dentition, subdivision of the CL morphology into vermillion notch to two-thirds CL, two-thirds to subtotal CL, and complete CL appears to be an optimal subdivision. Our results indicate that a more detailed subdivision of the CL has clinical relevance and that critical factors in the pathogenesis of the CL are also critical for the odontogenesis.